Выбери меня: [роман] / Тесс Герритсен, Гэри Брейвер - Герритсен Тесс (Звезды мирового детектива, 2021)
Экземпляры: ф.18 (20240313) / Инвентарный номер: 4750 / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: Г 39 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-445.7